Surface modifications by both anodic oxidation and ion beam implantation on electropolished titanium substrates - Acciari, Heloisa A. [UNESP] (2019)
The purpose of this work is to investigate the superficial induced characteristics on titanium surface by anodic oxidation and ion beam implantation, i.e. two surface modification technologies, by focusing on variations in chemical composition, structure, morphology, wettability, and corrosion resistance in a simulated physiological solution. First, the films were obtained by anodization under experimental conditions determined by a previous work, on electropolished titanium substrates, in order to form uniform and crystalline TiO2 films. Afterwards, the surfaces were implanted by He ions using various doses (5.0 × 1015, 1.0 × 1016 and 1.0 × 1017 ions/cm2) at an energy of 150 keV. Scanning Electron Microscopy (SEM), Energy Dispersive Spectroscopy (EDS), Atomic Force Microscopy (AFM), Raman Spectroscopy, X-ray photoelectron spectroscopy (XPS), Water Contact Angle, and Electrochemical Measurements were employed to characterize the changes in the film induced by ions implantation, according to each dose. More information was also obtained by comparison with non-implanted samples and references therein. In general, the results obtained in this work suggest the He ion implantation produces a positive effect on the surface of the films, with respect to the hydrophilic properties, without drastically affecting the morphology and chemical composition.